Epidemiology, diagnosis and control of classical swine fever: Recent developments and future challenges. (10th August 2017) - Postel, Alexander; Austermann‐Busch, Sophia; Petrov, Anja; Moennig, Volker; Becher, Paul
Summary: Classical swine fever (CSF) represents a major health and trade problem for the pig industry. In endemic countries or those with a wild boar reservoir, CSF remains a priority for Veterinary Services. Surveillance as well as stamping out and/or vaccination are the principle tools of prevention and control, depending on the context. In the past decades, marker vaccines and accompanying diagnostic tests allowing the discrimination of infected from vaccinated animals have been developed. In the European Union, an E2 subunit and a chimeric live vaccine have been licensed and are available for the use in future disease outbreak scenarios. The implementation of commonly accepted and globally harmonized concepts could pave the way to replace the ethically questionable stamping out policy by a vaccination‐to‐live strategy and thereby avoid culling of a large number of healthy animals and save food resources. Although a number of vaccines and diagnostic tests are available worldwide, technological advancement in both domains is desirable. This work provides a summary of an analysis undertaken by the DISCONTOOLS group of experts on CSF. Details of the analysis can be downloaded from the web site athttp://www.discontools.eu/ .